2020
DOI: 10.1111/ane.13348
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stroke treatment after 6‐24 hours only needs non‐contrast CT

Abstract: If more than 6 hours have elapsed since the known onset of stroke symptoms, current guidelines for patients set forth by the American Heart Association (AHA) restrict class-IA recommendation to selected patients who have large vessel occlusion (LVO) in the anterior circulation and those cases where images and other eligibility criteria from the DAWN (DWI or CTP Assessment with Clinical Mismatch in the Triage of Wake-Up and Late Presenting Strokes Undergoing Neurointervention with Trevo) and DEFUSE-3 (Endovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…One out of 18 studies prospectively recruited patients 47. The majority of the remaining studies (n=13) conducted post-hoc analyses of prospective trial data or endovascular therapy registries, that is, patient and imaging characteristics were retrospectively reviewed according to different predefined triage models and reported along with efficacy and safety outcomes 48–59.…”
Section: Basic Imaging Selection Paradigms In the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…One out of 18 studies prospectively recruited patients 47. The majority of the remaining studies (n=13) conducted post-hoc analyses of prospective trial data or endovascular therapy registries, that is, patient and imaging characteristics were retrospectively reviewed according to different predefined triage models and reported along with efficacy and safety outcomes 48–59.…”
Section: Basic Imaging Selection Paradigms In the Literaturementioning
confidence: 99%
“…Study populations of all studies comprised patients who had an acute ischaemic stroke with a large vessel occlusion (internal carotid artery, middle cerebral arteryM1, middle cerebral artery M2; one study also involved posterior territory occlusions48) which had presented 6–24 hours after onset of stroke symptoms or last known well. Studies providing group comparisons adhered to either of two principle study designs: (1) patients meeting the criteria of a basic imaging paradigm presenting 6–24 hours after stroke onset (basic LATE -group) were compared with patients routinely selected for endovascular therapy without the use of advanced imaging within 6 hours of stroke onset (basic EARLY -group) according to guidelines (n=5),47 49 52 60 62 or (2) within 6–24 hours after stroke onset, patients who fulfilled basic imaging criteria (late BASIC -group) were compared with patients meeting perfusion imaging criteria (late CTP -group) that matched or closely referred to the DAWN/DEFUSE3 selection criteria (n=10) 48 50 53–60 63. Seven studies additionally reported outcome data of patients not treated with endovascular therapy 47 48 51 53 55 58 64…”
Section: Basic Imaging Selection Paradigms In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…5 6 Moreover, patients with LVO in the extended time window can potentially benefit from EVT selected by simpler imaging triage. [7][8][9][10][11] Collateral vasculature status is important to compensate blood flow to the ischaemic area when the principal supplying arteries are occluded. 12 Good collaterals are related to limited ischaemic core and favourable clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%